2020
DOI: 10.1159/000508787
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Diagnosis of Hidradenitis Suppurativa and Its Effect on Patients and Healthcare System

Abstract: Background: Hidradenitis suppurativa (HS) is a neglected chronic inflammatory disease with long delay in diagnosis. Besides pain, purulent discharge, and destruction of skin architecture, HS patients experience metabolic, musculoskeletal, and psychological disorders. Objectives: To determine the delay in HS diagnosis and its consequences for patients and the healthcare system. Methods: This was a prospective, multicenter, epidemiologic, non-interventional cross-sectional trial carried out in Germany and based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
133
0
17

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(153 citation statements)
references
References 32 publications
(39 reference statements)
3
133
0
17
Order By: Relevance
“…Such disease consequences have a substantial negative impact on general and skin-specific QoL [ 13 , 14 ]. Hidradenitis suppurativa is frequently misdiagnosed with an average duration from manifestation of first symptoms until diagnosis reported of 10.0 ± 9.6 (mean ± standard deviation) years despite the existence of published diagnostic criteria [ 5 , 15 17 ]. Because of the multifaceted nature of the disease, its course can be unpredictable, which poses challenges for patients and healthcare professionals (HCPs) in the management of the disease [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Such disease consequences have a substantial negative impact on general and skin-specific QoL [ 13 , 14 ]. Hidradenitis suppurativa is frequently misdiagnosed with an average duration from manifestation of first symptoms until diagnosis reported of 10.0 ± 9.6 (mean ± standard deviation) years despite the existence of published diagnostic criteria [ 5 , 15 17 ]. Because of the multifaceted nature of the disease, its course can be unpredictable, which poses challenges for patients and healthcare professionals (HCPs) in the management of the disease [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“… 15 A postponed professional attention, diagnosis and treatment may result in a more severe disease that, in turn may result in extensive destruction of skin architecture, scarring, impaired health status and professional life, and even higher number of concomitant systemic disorders as seen in acne 16 and hidradenitis supporativa. 17 The health practitioners have to be aware of alarming situations of this kind and take necessary measures to prevent possible exacerbations in case of a national crisis. This has become especially evident in the midst of the recent COVID-19 pandemic, when the health systems in most countries had to rapidly adjust to providing routine care to citizens under strenuous conditions of a worldwide crisis.…”
Section: Discussionmentioning
confidence: 99%
“…Hidradenitis suppurativa (HS) is a chronic inflammatory disease of the skin that affects around 1% of the general population [ 2 ] and it has an estimated prevalence of 1 to 4% [ 3 ]. It has been noticed that lack of awareness led to this disease being misdiagnosed often, especially in the early stages, or diagnosed late, with an average of 7 years [ 3 , 4 ]. HS can present in many people, where an appropriate early recognition and diagnosis are important to help patients understand the situation and ensure prompt disease management [ 5 , 6 ] to avoid an increase in the development of patients’ secondary psychiatric disorders, for instance, anxiety and depression, that could eventually lead to a higher risk of suicide [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…The progression of the disease is rapid during the period of misdiagnosis or late recognition, where the disease leads to minor inflammations until the destruction of the skin tissues. The only treatment for such conditions is to undergo surgical removal of the skin on the infected site [ 4 ]. Surprisingly, a recent report revealed that the unemployment rate of the patients diagnosed with HS is 25.1% as compared to the control population at 5.9% [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation